Pathologic features and differential diagnosis of chronic hepatitis. Issue 1 (January 2023) - Choi, Won-Tak; Gill, Ryan M.
Abstract: Persistent or relapsing hepatitic liver injury for more than 6 months results in chronic hepatitis, a broad category that includes the most common liver diseases: viral hepatitis, autoimmune hepatitis, drug-induced liver injury, and fatty liver disease, as well as less common inherited metabolic disorders such as Wilson disease and alpha-1-antitrypsin deficiency. Chronic cholestatic liver disease may also progress to advanced fibrosis and can be mistaken for a chronic hepatitis. Histologic features may overlap, especially at an advanced stage, and thus morphologic findings together with the overall clinical context play a critical role in establishing an accurate diagnosis. This review describes pathologic and clinical features of a spectrum of hepatitic liver disease that can cause chronic hepatitis, as well as diagnostic testing used to establish a diagnosis or distinguish among these entities.